PENGEMBANGAN MESIN PENGHANCUR KACA DENGAN METODE DESIGN FOR MANUFACTURE AND ASSEMBLY (DFMA) - NAUVAL ALFAN FACHRIZAL; NUR CHOLIS; FAHRUDIN (2021)
Indonesia has a waste problem that has peaked as a national level issue. Glass is one of the anorganic waste that holds the biggest part of household and industry waste. According to the 26 big cities in Indonesia, Indonesia produces 38,5 million tons of waste per year. The glass recycler has proven to be saving 18% of the total energy used to make new glasses. The importance of glass recycler in solving waste issue as well as increasing the efficiency in the glass production make the author wants to optimize the existing glass-shredder machine using DFMA method. This method simplifies the assembly process, manufacturing time, and decrease the assembly cost as well. The result of this study found that DFMA method could decrease the machine's dimension to 105 x 50 x 110 cm. Furthermore, there are few changes in order to simplify the component's shape to eliminate the components that doesn't have a significant role to get a decreased production time and cost. The DFA's indection in this study found to be greater in terms of efficiency that reached to 3,6% and also found to be smaller in the production cost which is RP 12,342,000 compared to the existing machine.